Growth and Characterization of Vacuum Annealing AgCuInSe2 Thin Film - Hameed Athab, Rana; Hussein, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The influence of annealing on quaternary compound Ag0.9Cu0.1InSe2 (ACIS) thin film is considered a striking semiconductor for second-generation solar cells. The film deposited by thermal evaporation with a thickness of about 700 nm at R.T and vacuum annealing at temperatures (373,473) K for 1 hour. It was deposited in a vacuum of 4.5*10-5 Torr on a glass substrate. From XRD and AFM analysis, it is evident that Ag0.9Cu0.1InSe2 films are polycrystalline in nature, having ideal stoichiometric composition. Structural analysis indicated that annealing the films following the deposition resulted in the increasing polycrystalline phase with the preferred orientation along (112) direction. , increasing crystallite size and average grain size after annealing . The optical properties of these films are determined by the wavelength between 400 nm – 1000 nm. The band gap of the Ag0.9Cu0.1InSe2 films was evaluated to be (1.68-1.5) eV, and the optical constants calculated, such as the refractive index, the extinction coefficient, and the real and imaginary parts of the dielectric constant.